جینۆسایدی بەری مەرگە و دۆڵی جافایەتی سااڵنی )١٩٨٨-١٩٨٥( - شوانی, پ. ی. د. ئاکۆ عەبدولکەریم; عەزیز, شاباز محەمەد (Sulaimani Journal for Humanities, 2024)
In this study (Marga and Dolly Jafayaty's genocide in (1985- 1988)) it is aimed to recognise the genocide process as the worst mass killing against humanity terminologically, theologically and other ways which aimed to destroy economy, infrastructure, race and religion of the areas. The study also shows the attempts to erase historical and cultural traces, and trying to impede the improvment of Kurdistan generally, Dolly Jafayaty and Marga area especially. These areas became the first field for commiting Anfal process of Kurdistan 13 | zsb.univsul.edu.iq JZSB p-ISSN: 1813-0852, e-ISSN: 2617-3034 گۆڤاری زانکۆی سلێمانی - (بەشی B - زانستە مرۆڤایەتییەکان) The study also highlights the raids and bloodshed done by Iraq regime through using internationally prohibited weapons remarkably mass killing ones. Having PUK leadership and other revolutionist party hubs gave the regime the pretext to siege and destroy the areas and remove their residants from their homes under the name of national and border security laws. The end of the study talks about negative effects of Anfal process, as well as destruction of Kurdistan nature and traumatized survivors. This research aims to conduct detailed scientific research on ethnic cleansing in the Beri Marja and Wadi Gviati region and to list the consequences, effects and tragedies of these events and the descriptive and historical methods used in writing this research